Gerakan Literasi Sekolah (GLS): Membudayakan Gemar Membaca di MI/SD - Zaenol Fajri; Ryan Nuraini; Fadilah Lutfi; Holidatul Munawaroh; Robihatul Fitriyah; Siti Maghfiroh Fawaid; Virna Budiarti (Jurnal Medika: Medika, 2025)
Literacy is a fundamental skill that everyone needs in the age of globalization.  However, a lack of passion, resources like libraries and reading nooks, creativity in literacy activities, and the less-than-ideal roles of parents and teachers all contribute to low reading interest among primary school pupils.  Additionally, pupils' focus is shifted from books to less instructive digital content when they use gadgets.  The School Literacy Movement (GLS) program is conducted in a contextual and participatory manner to address this.  The first steps are outreach, reading interest mapping, literacy team formation, and the implementation of regular activities like reading for 15 minutes before class, setting up reading nooks in schools, celebrating monthly Literacy Days, and hosting literacy contests.  Teachers and parents are also given training to help them better support their children's reading.  Books are supplied by contributions, partnerships with publishers, and independent acquisition based on the age range of the students.  To track the growth of reading interest and the program's efficacy, periodic assessments are carried out.  The findings indicate that kids' interest in reading has significantly increased.  Engaging reading programs and the participation of all school components contribute to its accomplishment.  A systematic monitoring system guarantees the program's viability, despite ongoing issues including inadequate facilities and unequal family participation distribution.  It is advised that GLS be extended to further schools with more training and improved literacy resources to develop a literate generation, motivated by its success in promoting reading habits in elementary and middle schools.